The Integration of the Cambridge and Merdeka Curricula in Shaping Islamic Character - Fauzi, Muhamad; Wulandari, Widya; Thoha, Anis Malik (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
The urgency is increasingly pressing amidst the complexity of environmental and social problems in dealing with the threat of diversity. Therefore, the integration of the Cambridge Curriculum and the Merdeka Curriculum is essential as it supports the quality of education and character development of students in facing global challenges. This study was conducted at SMAN South Sumatra. This research aims to analyze the integration of the Cambridge Curriculum and the Merdeka Curriculum in shaping Islamic character at SMAN South Sumatra. This research employed a qualitative approach with descriptive methods. Data were collected through interviews, documentation, and observation. The results of the research show that the implementation of the character formation program at SMAN South Sumatra found that all activities were integrated into the character formation program and had a significant influence. Apart from that, it can be applied practically in Islamic religious learning, developing a more adaptive curriculum, as well as theoretical contributions to the understanding of Islamic character formation in the curriculum in the current era.